Rhodium-Catalyzed Decarbonylative Intramolecular Arylation of 2-(1H-Indole-1-carbonyl)benzoic Acids - Suzuki, Hirotsugu; Takemura, Yosuke; Matsuda, Takanori (Synlett, 2024)
We developed a redox-neutral synthesis of isoindoloindolone via intramolecular arylation of 2-(1H-indole-1-carbonyl)benzoic acids. This protocol facilitates the formation of various substituted isoindoloindolones in yields ranging from 17% to 80%. Our mechanistic investigations indicate the pivotal role of NaI: the iodide anion promotes the formation of the desired isoindoloindolone, and the sodium cation suppresses the formation of acylated byproducts, thereby enabling the selective formation of isoindoloindolones in acceptable yields.
Keywords: rhodium; intramolecular arylation; mixed anhydride; isoindoloindolones; C–H activation; indoles